Development of artificial intelligence and multi-sensor-based dexterity assessment system: performance evaluation - Aktan, Mehmet Emin; Kilic, Sena Zeybek; Akdogan, Erhan; Misirlioglu, Tugce Ozekli; Palamar, Deniz (SPRINGER HEIDELBERG, 2025)
Manual dexterity tests are essential for diagnosing diseases and evaluating professional skills that require fine motor control. Traditional assessments often depend on expert supervision, leading to delays, subjectivity, and inaccuracies. This study introduces an automated dexterity assessment system that integrates multiple sensors and artificial intelligence algorithms for high-precision evaluation. The system classifies hand movements, analyzes muscle contraction levels, and determines hold-release durations using electromyography (EMG), inertial measurement units (IMU), and image processing techniques. An expert system interprets the multimodal sensor data and presents the results to clinicians. A performance evaluation with 20 participants demonstrated the system's capability to assess hand dexterity automatically and accurately.
Keywords: Wearable sensors; Dexterity test; Electromyography; Artificial neural networks; Image processing; MOTION; REHABILITATION; Computer Science; Engineering; Mathematical & Computational Biology; Medical Informatics